The Influence of Assistance of Helped Guided Inquiry Methods Tutorial Video Practicum on the Process of Student Science Skills (Journal of Innovative Science Education, 2019)
Interesting learning methods and media can support the learning process being fun and improve students' skills. This study aims to determine the effect of guided inquiry methods assisted by video practicum tutorials on science process skills, cooperative skills and student responses. The study was conducted in Jepara Middle School 5 2018/2019 school year. The population of the study was 9th grade students. Determination of the sample with a cluster random sampling system so that two classes are obtained to be sampled. The experimental class received treatment using guided inquiry methods assisted by practical tutorial video and control classes using guided inquiry methods. Hypothesis testing using t-test. Based on the results of the analysis, it was found that: (1) There were differences results of significant scientific process skills between guided inquiry learning assisted by video practicum tutorials compared to guided inquiry learning; (2) The results of collaboration skills observation between guided inquiry learning assisted by practical video tutorials are better than guided inquiry learning; (3) Students show a very good respond (average score of all students 115). By using interesting and fun learning media, it can make students be motivated and interested in learning.